1991
DOI: 10.1128/jvi.65.11.6094-6100.1991
|View full text |Cite
|
Sign up to set email alerts
|

Persistent human immunodeficiency virus type 1 infection in human fetal glial cells reactivated by T-cell factor(s) or by the cytokines tumor necrosis factor alpha and interleukin-1 beta

Abstract: Human immunodeficiency virus type 1 (HIV-1) infection of the brain has been associated with a severe dementing illness in children and adults. However, HIV-1 antigens are most frequently found in macrophages and microglial cells. To determine the extent of susceptibility of neuroglial cells to infection, the HIV-1 genome was introduced into cells cultured from human fetal brain tissue. Astroglial cells rapidly transcribed the viral genome producing high levels of p24 protein and infectious virions which peaked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(75 citation statements)
references
References 34 publications
5
70
0
Order By: Relevance
“…The physiological relevance of this observation is still unclear since astrocytes in the adult brain are normally quiescent and proliferate only following traumatic, ischemic, and inflammatory insults (Pekny and Nilsson, 2005). Nevertheless, our findings might help to explain the gradual disappearance of virus production over time reported by some studies (Luo and He, 2015;Tornatore et al, 1991).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The physiological relevance of this observation is still unclear since astrocytes in the adult brain are normally quiescent and proliferate only following traumatic, ischemic, and inflammatory insults (Pekny and Nilsson, 2005). Nevertheless, our findings might help to explain the gradual disappearance of virus production over time reported by some studies (Luo and He, 2015;Tornatore et al, 1991).…”
Section: Discussionmentioning
confidence: 62%
“…The concept of HIV-1 latency in astrocytes is also unclear and controversial. It has been shown that HIV-1 can achieve a state of dormancy in astrocytes and can be reactivated by a treatment with tumor necrosis factor (TNF) or interleukin (IL)-1b to produce infectious virus particles (Atwood, Tornatore, Meyers, & Major, 1993;Atwood et al, 1994;Tornatore, Meyers, Atwood, Conant, & Major, 1994;Tornatore, Nath, Amemiya, & Major, 1991). However, most of these data were obtained following transfection of HIV-1 DNA in established cell lines, which may not adequately represent in vivo conditions where proviral DNA is integrated into the host genome.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of original neural cells can, in general, be very different from those of cell lines, especially in the case of neurons. Recently it has been reported that primary brain culture are useful for studying the neurotropism of some viruses, for example, coronaviruses [13] and human immunodeficiency virus [10,16]. In order to investigate the neurotropism of JEV, we adapted a procedure for the…”
mentioning
confidence: 99%
“…Studies of both proliferating and resting cultures led to the conclusion that virus replication occurred mainly, if not exclusively, in DNA-synthesizing EC. This observation is consistent with studies of HIV-1-infected T cells showing that virus entry and expression are influenced by cell activation [Levy, 19931. In fact, the preintegration complex must be transported to the nucleus by an energy-requiring process [Bukrinsky et al, 19931 and viral gene expression is activated by nuclear factors of the cell that are also induced by exogenous stimuli such as IL1 and TNF-a [Tornatore et al, 1991;Poli and Fauci, 19921. The transient nature of HIV replication in EC cannot be explained by the fact that cultures were trypsinized after virus-cell contact, since this same procedure was capable of initiating the persistent infection of different cell types and was used to demonstrate the de novo production of virus [Tang and Levy, 1991;Dolei et al, 1994;Toniolo et al, 19951. In contrast to what has been observed in the EC infection with other viruses [Pensiero et al, 1992;Ramsay et al, 19931, the experiments with cytokine-neutralizing antibodies indicated that the production of endogenous cytokines does not downregulate the HIV permissiveness of HUVEC.…”
Section: Discussionmentioning
confidence: 99%